Boganmeldelser - Jesper Berning; Thorkil Thorsen; Britta Kyvsgaard; Torstein Eckhoff; Arne Baun; Ruth Nielsen; Signe Justesen; Marie.Louise Andreasen (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews